Cultural adaptation of meaning-centered psychotherapy for latino families: a protocol. Issue 4 (4th April 2022) - Torres Blasco, Normarie; Costas Muñiz, Rosario; Zamore, Carolina; Porter, Laura; Claros, Maria; Bernal, Guillermo; Shen, Megan Johnson; Breitbart, William; Castro, EM
Abstract : Introduction: Literature suggests couple-based interventions that target quality of life and communication can lead to positive outcomes for patients with cancer and their partners. Nevertheless, to date, an intervention to address the needs of Latino families coping with advanced cancer has not been developed. Meta-analytic evidence suggests that culturally adapted evidenced-based intervention targeting a specific cultural group is four times more effective. Our goal is to culturally adapt a novel psychosocial intervention protocol entitled ' C aregivers-P a tients S upport to L a tinx coping advanced-cancer' (CASA). We hypothesised that combine two evidence-based interventions and adapting them, we will sustain a sense of meaning and improving communication as patients approach the end of life among the patient–caregiver dyad. Methods and analysis: To culturally adapt CASA, we will follow an innovative hybrid research framework that combines elements of an efficacy model and best practices from the ecological validity model, adaptation process model and intervention mapping. As a first step, we adapt a novel psychosocial intervention protocol entitled protocol entitled ' C aregivers-P a tients S upport to L a tinx coping advanced-cancer' (CASA). The initial CASA protocol integrates two empirically based interventions, meaning-centred psychotherapy and couple communication skills training. This is an exploratory and prepilot study, and it is not necessary for a size calculation. However, based on recommendations for exploratory studies of this nature, a priori size of 114 is selected. We will receive CASA protocol feedback (phase 1b: refine) by conducting 114 questionnaires and 15 semistructured interviews with patients with advanced cancer and their caregivers. The primary outcomes of this study will be identifying the foundational information needed to further the develop the CASA (phase IIa: proof-of-concept and phase IIb: pilot study). Ethics and dissemination: The Institutional Review Board of Ponce Research Institute approved the study protocol #1907017527A002. Results will be disseminated through peer-reviewed publications.